Quantitative proteomics reveals Polygonum perfoliatum L. ameliorates hepatic steatosis by promoting PPARs/CPT1A/CPT2-mediated fatty acid β-oxidation - Liu, Guanjie; Chang, Ling; Qian, Yihan; Lin, Jiacheng; Shang, Zhi; Xu, Min; Wang, Fang; Sun, Xuehua; Jiang, Yun; Gao, Yueqiu; Kong, Xiaoni (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a prevailing cause of end-stage liver disease in the coming decades. Polygonum perfoliatum L. (PPL) is a medicinal herb with anti-lipid peroxidation and anti-inflammatory properties, exerting a hepatoprotective effect. However, the protective effect of PPL against NAFLD and its underlying mechanism remain incompletely understood. Here, we show that PPL protects high fat diet (HFD)-induced hepatic steatosis, lipid peroxidation, and glucose-lipid metabolism dysfunction in NAFLD mice. We performed a label-free quantitative proteomic profiling to determine the effect of PPL treated the proteomics profile of liver tissue and identified activated PPARs/CPT1A/CPT2-mediated hepatic fatty acid β oxidation (FAO) process was significantly altered. In vitro treatment of hepatocytes with PPL extract confirmed these altered process and FAO inhibitor Etomoxir (ETO) attenuated the lipid-lowering activity of PPL extract in hepatocytes. Ultra-high-performance liquid chromatography/ Q Exactive-HFX (UPLC/QE-HFX) was used to determine the material basis for PPL against NAFLD. Our results demonstrated the effects and potential mechanisms of PPL as an effective pharmacological treatment of NAFLD.